A systematic review: the application of virtual reality on the skill-specific performance in people with ASD. Issue 2 (17th February 2023) - Mak, Grace; Zhao, Lea
ABSTRACT: Given the prevalence of Autism Spectrum Disorder (ASD) and the demand for treatment, there is a continuous seeking and uncertainty of effective interventions for people with ASD. As technology continues to advance, the application of Virtual Reality is emerging in clinical settings. This systematic review summarised findings to evaluate the application of virtual reality (VR) on the skill-specific performance in people with ASD. The purpose is to determine (1) if VR is an effective treatment for people with ASD in skill-specific performance and (2) can Occupational Therapists employ VR in their practice. Eight databases were systematically searched for peer-reviewed articles that were published from January 2012 to February 2018. Eight articles met the inclusion criteria. The measurements of specific skills were categorised into three main domains: job interviewing, driving, and other ADLs. A diverse range of outcome measures were utilised and provided various results. Despite the consistent positive results reported in the studies, the current evidence base lacks justification of sample sizes, reliability and validity of the findings. Although VR shows potential as an effective intervention, limitations and bias of studies should be considered. Results of studies must be interpreted with caution if Occupational Therapists are interested in employing VR in their practice.